Social vulnerability and some considerations regarding crime committed by minors in Costa Rica - Flores-León, Thelmo (Latin American social work in the justice system, 2023)
This chapter analyzes some of the approaches and variables to consider in the social evaluations of adolescents in criminal proceedings. It highlights the perspective of clinically assessing dangerousness and clinically assessing vulnerability and highlights how these approaches are applied not only for diagnostic purposes but also for the treatment of juvenile offenders. Other important concepts in adolescent development are also discussed here, and some theories of criminal behavior and how they can be relevant in the approach of social work with adolescents in the penal system are described.